HDAC6 is associated with the formation of aortic dissection in human - Xian Guo; Ze-Min Fang; Xiang Wei; Bo Huo; Xin Yi; Cai Cheng; Jun Chen; Xue-Hai Zhu; Anas Omar Khalil Abu Bokha; Ding-Sheng Jiang (Molecular Medicine, 2019)
Abstract Background The pathological features of aortic dissection (AD) include vascular smooth muscle cell (VSMC) loss, elastic fiber fraction, and inflammatory responses in the aorta. However, little is known about the post-translational modification mechanisms responsible for these biological processes. Methods A total of 72 aorta samples, used for protein detection, were collected from 36 coronary artery disease (CAD, served as the control) patients and 36 type A AD (TAAD) patients. Chromatin immunoprecipitation (ChIP)-PCR was used to identify the genes regulated by H3K23ac, and tubastatin A, an inhibitor of HDAC6, was utilized to clarify the downstream mechanisms regulated by HDAC6. Results We found that the protein level of histone deacetylase HDAC6 was reduced in the aortas of patients suffering from TAAD and that the protein levels of H4K12ac, and H3K23ac significantly increased, while H3K18ac, H4K8ac, and H4K5ac dramatically decreased when compared with CAD patients. Although H3K23ac, H3K18ac, and H4K8ac increased in the human VSMCs after treatment with the HDAC6 inhibitor tubastatin A, only H3K23ac showed the same results in human tissues. Notably, the results of ChIP-PCR demonstrated that H3K23ac was enriched in extracellular matrix (ECM)-related genes, including Col1A2, Col3A1, CTGF, POSTN, MMP2, TIMP2, and ACTA2, in the aortic samples of TAAD patients. In addition, our results showed that HDAC6 regulates H4K20me2 and p-MEK1/2 in the pathological process of TAAD. Conclusions These results indicate that HDAC6 is involved in human TAAD formation by regulating H3K23ac, H4K20me2 and p-MEK1/2, thus, providing a strategy for the treatment of TAAD by targeting protein post-translational modifications (PTMs), chiefly histone PTMs.